How to propel domestic tourism activity in an industrial city through wine tourism: A project based in the state of Aguascalientes, Mexico - Espino Mendoza, Sandra (2022)
It is widely known that wine cellars are among the most appealing destinations for tourists, especially when visiting a European country. However, vineyard visitation is not an isolated popular tourism activity when it comes to New World countries. Although some research developed in Australia and Argentina have demonstrated an increment in wine tourism demand, this type of tourism is still an under-investigated economic activity in Mexico. Thus, this project aims to investigate if wine tourism could be a viable attraction to propel tourism activity in an industrial city, its potential as a booming market in the country, and its possible enhancements. To analyse this premise, the state of Aguascalientes, Mexico, was taken as the case study destination due to its scarcity of tourism activity, its long-standing wine-producing tradition, and its developing wine route. Secondary data from the literature review and primary data gathered from a focus group were analysed to prove this theory. The qualitative and quantitative information obtained revealed that wine tourism is appealing enough for tourists to visit an industrial destination under the proper conditions. Furthermore, it was possible to develop specific managerial and marketing recommendations for the wine tourism sector in Aguascalientes to make it a competitive wine tourism destination in the country, presenting it as an introductory wine tourism destination for wine-novice tourists.